2020
DOI: 10.1111/are.14779
|View full text |Cite
|
Sign up to set email alerts
|

Hydroponic horticulture using residual waters fromOreochromis niloticusaquaculture with biofloc technology in photoautotrophic conditions withChlorellamicroalgae

Abstract: Protein‐dependent aquaculture generates large amounts of nutrient‐rich residuals; a feasible way to develop sustainable production systems is to integrate Decoupled Aquaponic Systems (DAPS) with residual water bioprocesses, to combine Photoautotrophic Biofloc Technology (P‐BFT) aquaculture and hydroponic horticulture. This study describes the characteristics of residual water from Oreochromis niloticus aquaculture performed with P‐BFT inoculated with Chlorella microalgae, reared during the nursery (180 fish m3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 78 publications
(122 reference statements)
0
11
1
Order By: Relevance
“…Additionally, recent studies have evaluated the macro-and micro-nutrients available in the water and the solid portion (visible biomass) of FLOCponics systems, in an attempt to minimize uncertainty in predictions. 48,123,124,134 In general, lower concentrations of nutrients in FLOCponics water as compared to hydroponic solutions have been found. 123 On the other hand, when compared to traditional aquaponics using RAS, higher concentrations of P, K, Ca, S and Fe were found and seem to be associated with the practice of external carbon addition.…”
Section: Water Quality and Nutrient Recyclingmentioning
confidence: 98%
See 4 more Smart Citations
“…Additionally, recent studies have evaluated the macro-and micro-nutrients available in the water and the solid portion (visible biomass) of FLOCponics systems, in an attempt to minimize uncertainty in predictions. 48,123,124,134 In general, lower concentrations of nutrients in FLOCponics water as compared to hydroponic solutions have been found. 123 On the other hand, when compared to traditional aquaponics using RAS, higher concentrations of P, K, Ca, S and Fe were found and seem to be associated with the practice of external carbon addition.…”
Section: Water Quality and Nutrient Recyclingmentioning
confidence: 98%
“…The influence of nutrient uptake by BFT microorganisms on the availability of nutrients for plant production is yet unclear. At this moment, the results have indicated that running a mixotrophic or chemoautotrophic BFT would be the best option for FLOCponics systems 134,140 due to the expected predominance of nitrifying communities (higher concentration of nitrate in water) instead of a heterotrophic‐based medium. Another approach related to BFT microorganisms that must be clarified is whether a thin flocs biofilm on plant roots has the potential to boost or harm the nutrient uptake by the plants.…”
Section: Challenges Of Flocponics Systemsmentioning
confidence: 99%
See 3 more Smart Citations